Uji Nanoemulsi Ecoenzym Terhadap Bakteri Staphylococcus aureus - anindita, Reza; Nathalia, Dede Dwi; Beandrade, Maya Uzia; Putri, Intan Kurnia; Sari, Afrinia Eka; Setyodewi, Elisabeth (Fakultas Matematika & Ilmu Pengetahuan Alam - Universitas Islam Malang, 2024)
The discovery of eco enzyme as a fermented liquid from organic vegetable and fruit waste has been used as an organic plant fertilizer, disinfectant, hand sanitizer, antiseptic soap, and domestic waste degradation agent. However, trials of eco enzymes as raw materials for health preparations have not yet been carried out. Seeing this, trial research is needed on the use of ecoenzyme nanoemulsion against Staphylococcus aureus bacteria. This research aims to determine the antibacterial ability of ecoenzyme nanoemulsion against S. aureus bacteria. The design of this research is experimental. The samples used were ecoenzyme nanoemulsions with Formula 1 (F1) 20%, Formula 2 (F2) 25%, and Formula 3 (F3) 30%. This research includes making ecoenzyme, making ecoenzyme nanoemulsion, testing ecoenzyme nanoparticles, and testing ecoenezyme nanoemulsion against S. aureus bacteria using the Kirby-Baeur method. The results showed that the sizes of ecoenzyme nanoparticles in F1 20%, F2 25%, and F3 30% were 38.9 nm, 65.07 nm, and 146.2 nm, respectively. The results of the antibacterial ability test of nanoemulsion eco enzyme F1 20%, F2 25%, and F3 30% against S. aureus produced an inhibitory zone 4.3 mm (resistant), 4.3 mm (resistant), and 6.7 mm (resistant). This research concludes that the eco enzyme nanoemulsion is not effective in inhibiting the growth of S. aureus bacteria.